Indo-European and common Germanic roots of the preterito-presentia verbs - Боцман, А. В.; Моренець, І. М. (Studia Philologica, 2019)
The article addresses the Indo-European and common Germanic roots of the preterito-presentia verbs. The words of the ancient Indian, Greek, Latin, Old Slavonic, Lithuanian, Gothic, Old English, Old High German, Old Saxon, and Old English languages are analysed within the framework of the comparative-historical approach. The analysis is carried out on the phonological, morphological and semantic levels. The main attention is paid to the discovery of common latent archaic roots that were obscured in the process of historical development and the separation of the Germanic language group from the rest of the Indo-European language family.